Farewell, my beautiful homeland - Ümit, Ahmet, 1960- (Anthem Press, 2020)
'Farewell, My Beautiful Homeland' is the story of a man from Salonika on the eve of the First World War who is forced to choose between his love for a woman and his love for his country as the Ottoman Empire is drawn into the war and faces collapse.